Development of Comic-Based Physics Modules to Improve Students' Critical Thinking Ability on Vibration and Wave Materials - Yuliana Nensi Putri; Nurul Ain; Kurriawan Budi Pranata (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2022)
This development research will produce a product in the form of a comic-based physics module on vibration and wave material. The research objectives are to determine: (1) Feasibility, (2) practicality, and (3) the effectiveness of the module to improve students' critical thinking skills. The research uses Research & Development which refers to the development of ADDIE namely Analysis, Design, Development, Implementation and Evaluation. The analysis and design stages are developed based on the needs of students by displaying the discussion of comic characters which aims to make students able to think critically. The product validation stage involves 4 validators, namely two media experts and 2 material experts to assess the module design, material feasibility, and language feasibility. The results of the validation of the feasibility of the module obtained 82% from the 2 media experts and 82% from the 2 material experts--all of which were within the category of "Very Valid". The implementation phase was carried out at SMP Negeri 2 Wagir with 26 students of class VIII as the subject. The results of the study are: (1) the practicality of the module is 93% within the "Very Positive" category for the 26 student responses, while for the physics teachers, it is 95% within the "Very Positive" category; (2) the effectiveness of the module is indicated by an increase in students' critical thinking skills with an N-gain of 0.68 under the "Medium" category of improvement. Thus, it can be concluded that the comic-based physics module produced in this study is suitable for use in learning vibration and wave materials.